Use Of Panty Liner As A Risk Factor The Occurration Of Abnormal Vaginal Discharge - Aurellia, Leviana; Nainggolan, Julita (Medicinus, 2021)
Vaginal discharge or fluor albus is a problem that is often found in women. Daily use of panty liner is a predisposing factor of pathological/abnormal vaginal discharge. This paper reviews the correlation between the use of panty liner and vaginal discharge. The aims of this study were to analyze the effect of daily panty liner use as a risk factor of vaginal discharge. This research is done by using the cross-sectional method. The study population is students of the University of Pelita Harapan in the Faculty of  Nursery. Sample size calculation was done using the categorical comparative analytical formula and a result of 46 samples were obtained for each population. A questionnaire was used in this research. Statistical analysis is done by using the SPSS 22.0 program with the Chi-Square method. Bivariate analysis on 92 respondents revealed that there is a significant association between the usage of a panty liner and abnormal vaginal discharge (p-value <0.05). Based on bivariate analysis panty liner material is not related to abnormal vaginal discharge (p-value >0.05).